The Effect of Product Attributes, Service Quality and Customer Satisfaction on Customer Loyalty (Case Study at Bank Mandiri KCP Palembang Km 5) - Mika Thania; Saripudin (PT FORMOSA CENDEKIA GLOBAL, 2023)
The objective of this research is to examine how customer loyalty is impacted by product attributes, service quality, and customer satisfaction. The data used primary data with the distribution of questionnaires of 100 respondents of Bank Mandiri KCP Palembang KM 5 customers using non-probability sampling techniques and purposive sampling methods. Type of associative research using quantitative with Structural Equation Modeling (SEM) Partial Least Square (PLS) method with SmartPLS 4.0 data processing tool. Customers' loyalty was positively and significantly impacted by product features, according to the results (0.000 < 0.05), service quality had a positive and significant effect on customer loyalty 0.000 < 0.05, customer satisfaction had a positive and significant effect on customer loyalty 0.045 < 0.05. Together, X1, X2, and X3 have a positive and significant effect on customer loyalty Fhitung (115,742) > Ftabel (2,70)